1981
DOI: 10.1017/s0001566000006589
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight in Twins Versus Singletons: Separate Entities and Different Implications for Child Growth and Survival

Abstract: The condition of low birth weight is compared in twins and in singletons in terms of birth weight distributions and with respect to factors such as the incidence of sillbirths, length of gestation, maternal age, parity, and legitimacy. In the light of demographic, biological, and developmental considerations, it is concluded that low birth weight in twins is a different condition from low birth weight in singletons and should be dealt with independently, especially in view of the different implications for chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…In contrast to the numerous reports on the gestational age and birth weight of singletons and twins (McKeown and Record, 1952;Powers, 1973;Gedda et al, 1981;Leroy et al, 1982;Watson and Campbell, 1986;Bonnelykke et al, 1987;Alfieri et al, 1987;Buckler and Buckler, 1987;Bleker et al, 1988;Keith 1994;Luke, 1996;Beiguelman et al, 1997), little is known of these traits in stillbirths and early neonatal deaths.…”
Section: Resultsmentioning
confidence: 94%
“…In contrast to the numerous reports on the gestational age and birth weight of singletons and twins (McKeown and Record, 1952;Powers, 1973;Gedda et al, 1981;Leroy et al, 1982;Watson and Campbell, 1986;Bonnelykke et al, 1987;Alfieri et al, 1987;Buckler and Buckler, 1987;Bleker et al, 1988;Keith 1994;Luke, 1996;Beiguelman et al, 1997), little is known of these traits in stillbirths and early neonatal deaths.…”
Section: Resultsmentioning
confidence: 94%
“…However, when looking at the twins' curves at 36-week gestational age, the curves from the populations of the three hospitals were practically the same, meaning that the etiology of prematurity and/or low birthweight in twins may be essentially mechanical, compared to singletons, where it is generally related to outer factors (Gedda et al, 1981). Only after 38-weeks gestational age did the three curves become different, reaching higher values according to the socioeconomic levels.…”
Section: Discussionmentioning
confidence: 94%
“…On average, twins are born with lower gestational age and lighter weight than singletons (Beiguelman et al, 1998;Bleker et al, 1988;Buckler & Buckler, 1987;Colletto et al, 2003;Gedda et al, 1981;Keith, 1994;Luke et al, 1991;Luke, 1996). When twins and singletons are distributed into three classes of birthweight (less than 1500g, between 1500 and 2500g, and more than 2500g), the proportion of newborns with low and very low birthweight is dramatically higher than that among singletons .…”
mentioning
confidence: 99%
“…Buekens et al [1] reported that the prognosis of low-birth-weight twin infants is better than that of the same-birth-weight singleton infants. Thus, lowbirth-weight or small-for-gestational-age (SGA) in twin pregnancies should be studied based on the twin pregnancy standard [1,3]. However, few investagions have examined large-for-gestational-age (LGA) in twin pregnancies.…”
Section: Introductionmentioning
confidence: 99%